2015
DOI: 10.1364/ol.41.000092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of residual phase gradients in optical null interference

Abstract: A scheme to study the effect of residual phase gradients in an optical interference between two out-of-phase Gaussian beams is proposed. In a Sagnac interferometer configured to provide a null output, a variable linear phase swept across the null point unfolds an optical field rotation due to an apparently negligible residual phase gradient present orthogonal to the linear phase sweep. As the optical beam that rotates around its propagation axis carries orbital angular momentum, the experimental results presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The splitting rotates to the horizontal plane at the Brewster angle and then towards the nearly vertical plane −45°(upper half) and 45°(lower half) but in a reversed way. This polarizationdependent beam-rotation behavior around the Brewster angle is reminiscent of field-rotation around singularities and in null-interferometers [33]. For LG beams in the second, third and forth rows, we have observed a similar rotation effect and additional spiraling behavior whose magnitude increases with the mode of LG beams.…”
Section: Discussion Of Resultssupporting
confidence: 66%
“…The splitting rotates to the horizontal plane at the Brewster angle and then towards the nearly vertical plane −45°(upper half) and 45°(lower half) but in a reversed way. This polarizationdependent beam-rotation behavior around the Brewster angle is reminiscent of field-rotation around singularities and in null-interferometers [33]. For LG beams in the second, third and forth rows, we have observed a similar rotation effect and additional spiraling behavior whose magnitude increases with the mode of LG beams.…”
Section: Discussion Of Resultssupporting
confidence: 66%
“…As mentioned earlier, different approaches are designed to compensate or overcome it. In the proposed interferometric approach of introducing lateral shear and linear phase difference in orthogonal directions between superposing out-of-phase Gaussian beams, a hinge-point thus appearing plays a crucial role 61 . The source of achromatic nature of the generated vortex can be easily understood from the well-known optical white-light interferometry.…”
Section: Discussionmentioning
confidence: 99%
“…From our recent investigations on optical null interference using Gaussian beams, we found that there is a more fundamental picture to the interferometric generation of an optical singularity beyond the view as a vortex array generator. The recent study on optical null interference has exemplified the role played by a pivot point in a two-Gaussian beam interference where the phase remains stationary and surrounding optical field undergoes a rotation in the presence of a phase ramp [24,25]. It is well known that the vortices are created and annihilated as dipoles.…”
Section: Introductionmentioning
confidence: 99%